Surgeon Knowledge of the Pulmonary Arterial System and Surgical Plan Confidence Is Improved by Interactive Virtual 3D-CT Models of Lung Cancer Patient Anatomies - Bhakhri, Kunal; Hyde, Eoin R.; Mak, Sze M.; Berger, Lorenz U.; Ourselin, Sebastien; Routledge, Tom; Billè, Andrea (Frontiers in Surgery, 2021)
Objective: Interactive three-dimensional virtual models of pulmonary structures (3D-CT) may improve the safety and accuracy of robotic-assisted thoracic surgery (RATS). The aim of this study was to evaluate the impact of 3D-CT models as an imaging adjunct on surgical confidence and anatomical assessment for lobectomy planning. Methods: We retrospectively analyzed the response of specialist thoracic surgeons who collectively reviewed 100 pre-operative images of patients undergoing robotic-assisted lobectomy lung cancer cases from June to November 2018 in our institute. The number of arteries, veins, and bronchi entering the resected lobes were determined from the operation video recording by the operating surgeon. 3D-CT models were generated for each case and made available for online visualization and manipulation. Thoracic surgeons were invited to participate in the survey which consisted of an evaluation of CT (control) and 3D-CT (intervention) models. A questionnaire regarding anatomical structures, surgical approach, and confidence was administered. Results: Ten participants were recruited. 3D-CT models led to a significant (p<0.003) increase in the surgeons’ ability to correctly identifying pulmonary arteries entering the resection lobes in 35% (CT) and 57% (3D-CT) of cases. A significant (p<1e-13) improvement in anatomy assessment and surgical plan confidence was observed for the 3D-CT arm, with median Likert scale scores of “2 - Slightly easy” (CT) and “4 - Very easy” (3D-CT). Conclusion: The use of 3D-CT models for thoracic surgery planning increases the surgeon's confidence in recognizing anatomical structures, largely by the enhanced appreciation of anatomical variations in the segmental pulmonary arterial system. Further studies are needed to investigate if 3D-CT models can be used in providing precise information about segmental artery distribution